Pengaruh Tax Audit, Tax Penalty, Laporan Audit, Dan Penerapan E_Filing Terhadap Kepatuhan Wajib Pajak - Vivi Nara Purba; Mei Eviyanti Br Nababan; Ayu Lovio Nitta Purba; Sauh Hwee Teng; Hantono Hantono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Taxpayeri compliancei is critical to the government's ability to increase tax collection year after year, making it a recurring difficulty for many Tax Offices (KPPs) throughout Indonesia. This study will look at the influence of tax audits, fines, audit reportsi, and e-filingi on taxpayeri complianceiat KPP Kotai Medan. The study's populationi consists of individuali taxpayers registered with the KPP in Medan City, with a sample size of 100 respondents drawn using the Lambesshow algorithm. Primary data is gathered through surveys. Data analysis makes use of multiplei linear regressioni, classical assumption tests, and hypothesis testing. The results show that tax audits, fines, and audit reports have no meaningful impact on taxpayer compliance, but e-filing does. Tax audits, fines, audit reports, and electronic filings all have a substantial influence on taxpayericompliance. Tax audits, fines, audit reportsi, and e-filingi all have a significant link with itaxpayer compliance, accounting for 55.4% of the variance, while the remaining 44.6% is most likely due to unknown variables.